Optimizing glass-ceramic bonding incorporating new silane technology in an experimental universal adhesive formulation. Issue 5 (May 2021) - Yao, Chenmin; Ahmed, Mohammed H.; De Grave, Lauren; Yoshihara, Kumiko; Mercelis, Ben; Okazaki, Yohei; Van Landuyt, Kirsten L.; Huang, Cui; Van Meerbeek, Bart
Graphical abstract: Highlights: New silane technology improved glass-ceramic bonding of a universal adhesive (UA). The experimental silane-containing UA outperformed its commercial precursor. Best bond durability remains achieved by HF etching followed by separate prior silanization. Abstract: Objective: Incorporating silane-coupling agent into universal adhesives (UAs) to simplify adhesive luting of glass-ceramic restorations appeared ineffective due to silane's instability in an acidic aqueous solution. This study aimed to evaluate new silane technology added to an experimental UA to be bonded to glass ceramics without separate prior silanization. Methods: Combined silane technology, consisting of 3-(aminopropyl)triethoxysilane (APTES) and γ-methacryloxypropyltriethoxysilane (γMPTES), was incorporated into an experimental UA formulation, being referred to as ADH-XTE (3M Oral Care). Immediate and aged shear bond strength (SBS) of ADH-XTE onto as-milled ('AM'), tribochemical silica-coated ('TSC'), HF-etched ('HF'), and mirror-polished ('MP') glass-ceramic CAD/CAM blocks (IPS e.max CAD) with/without separate silanization was measured (n = 10/group). The control adhesives included Scotchbond Universal ('SBU') and Scotchbond 1 XT ('SB1-XT'). The glass-ceramic surface topography and the fractography of the SBS-debonded specimens were observed by SEM. Results: Without separate prior silanization, the experimental UA ADH-XTE, containing combined APTES/γMPTES silane technology, significantly outperformed the glass-ceramic bonding efficiency of its silane-containing SBU precursor, while it performed equally effective as SBU applied with prior silanization. Upon aging, significant reduction in SBS was recorded when ADH-XTE was bonded to TSC glass-ceramic surfaces ( p < 0.05), while not to HF ones. Notably, the lowest SBS was obtained when the UAs were bonded to AM and MP glass-ceramic surfaces, in particular when applied without separate prior silanization ( p < 0.05). Significance: The glass-ceramic bonding capacity of the new combined APTES/γMPTES silane-containing UA ADH-XTE surpassed that of its SBU precursor. HF etching remains needed to durably bond to glass-ceramics.